Use of Gene-Expression Profiling to Identify Prognostic Subclasses in Adult Acute Myeloid Leukemia - Bullinger, Lars; Döhner, Konstanze; Döhner, Hartmut; Bair, Eric; Fröhling, Stefan; Schlenk, Richard F; Tibshirani, Robert; Pollack, Jonathan R (The New England journal of medicine, 2004)
This study demonstrates that the genes expressed by peripheral-blood monocytes of adults with acute myeloid leukemia provide prognostic information over and above that provided by established indicators such as cytogenetic status. The authors analyzed the gene-expression profiles of samples obtained from 116 patients, who were subsequently assigned to receive various intensive treatments. They identified good- and poor-outcome classes of gene expression that were associated with differences in overall survival — even when the analysis was restricted to specimens with a normal karyotype. Genes expressed by monocytes identified good- and poor-outcome classes even with a normal karyotype. Acute myeloid leukemia (AML) is the most common acute leukemia in adults. Chemotherapy induces a complete remission in 70 to 80 percent of younger patients (age, 16 to 60 years), but many of them have a relapse and die of their disease. Myeloablative conditioning followed by allogeneic stem-cell transplantation can prevent relapse, but this approach is associated with a high treatment-related mortality. 1 Therefore, accurate predictors of the clinical outcome are needed to determine appropriate treatment for individual patients. (See Glossary.) Currently used prognostic indicators include age, cytogenetic findings, the white-cell count, and the presence or absence of an antecedent hematologic . . .